2014
DOI: 10.1080/00221341.2013.869245
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Writing Abilities in Geography: Examining the Benefits of Criterion-Based Assessment and Detailed Feedback

Abstract: Poor quality writing skills among undergraduate geography students is a significant concern among university instructors. This article reports on a multipronged strategy aimed at improving student writing in a large, first-year human geography course. The strategy emphasized ways to provide effective feedback through teaching assistant training, criterion referenced assessment, draft and final submission, peer review, and in-class writing exercises. Writing activities focused on building geographic understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…Συνεπώς, το θέμα κάθε Γραπτής Εργασίας οφείλει να συνδράμει στην ανάπτυξη των δεξιοτήτων διανόησης και να συμβάλλει σύμφωνα με τη Φαναρίτη (2010) στη μαθησιακή αυτονομία των φοιτητών/-τριών μέσω των στοιχείων του ενδιαφέροντος, της κατανόησης, της σύνδεσης με τη θεωρία και της σαφήνειας των οδηγιών. Αντίστοιχα, καθώς τα κριτήρια αξιολόγησης ορίζουν το πλαίσιο μέσα στο οποίο γίνεται κατανοητή, έγκυρη και αξιόπιστη η διαδικασία της αξιολόγησης (Morais, 2002), πρέπει th International Conference in Open & Distance Learning -November 2017, Athens, Greece -PROCEEDINGS SECTION A: theoretical papers, original research and scientific articles να παρέχονται γραπτώς κατά τη διάρκεια της εκπόνησης της εργασίας, να είναι συγκεκριμένα για κάθε δραστηριότητα και να χαρακτηρίζονται από διαφάνεια ως προς το τι αξιολογείται, πώς αξιολογείται και γιατί αξιολογείται (Leydon, Wilson, & Boyd, 2014). Άλλωστε, τα κριτήρια οδηγούν, μεταξύ άλλων, στον εντοπισμό των βασικών εννοιών μιας εργασίας, στον ορισμό συγκεκριμένων στόχων προς επίτευξη και στην οργάνωση του σχεδίου (Bloxham & West, 2007).…”
Section: λέξεις-κλειδιά: πολυκείμενα γραπτές εργασίες εκπαιδευτικό unclassified
“…Συνεπώς, το θέμα κάθε Γραπτής Εργασίας οφείλει να συνδράμει στην ανάπτυξη των δεξιοτήτων διανόησης και να συμβάλλει σύμφωνα με τη Φαναρίτη (2010) στη μαθησιακή αυτονομία των φοιτητών/-τριών μέσω των στοιχείων του ενδιαφέροντος, της κατανόησης, της σύνδεσης με τη θεωρία και της σαφήνειας των οδηγιών. Αντίστοιχα, καθώς τα κριτήρια αξιολόγησης ορίζουν το πλαίσιο μέσα στο οποίο γίνεται κατανοητή, έγκυρη και αξιόπιστη η διαδικασία της αξιολόγησης (Morais, 2002), πρέπει th International Conference in Open & Distance Learning -November 2017, Athens, Greece -PROCEEDINGS SECTION A: theoretical papers, original research and scientific articles να παρέχονται γραπτώς κατά τη διάρκεια της εκπόνησης της εργασίας, να είναι συγκεκριμένα για κάθε δραστηριότητα και να χαρακτηρίζονται από διαφάνεια ως προς το τι αξιολογείται, πώς αξιολογείται και γιατί αξιολογείται (Leydon, Wilson, & Boyd, 2014). Άλλωστε, τα κριτήρια οδηγούν, μεταξύ άλλων, στον εντοπισμό των βασικών εννοιών μιας εργασίας, στον ορισμό συγκεκριμένων στόχων προς επίτευξη και στην οργάνωση του σχεδίου (Bloxham & West, 2007).…”
Section: λέξεις-κλειδιά: πολυκείμενα γραπτές εργασίες εκπαιδευτικό unclassified
“…This confers linguistic acquisition abilities, including grammatical accuracy, lexicon, syntax, organization, style, and rhetoric strategies (Ahangari & Babapour, 2015). It is as well as the punctuation errors reduction and the identifiable thesis statements increases between a draft to a final submission (Leydon, Wilson, & Boyd, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Written communication is one of the engineering skills, where there are strong indications of a mismatch between skills actually developed during university studies and the higher expectations found at workplaces (Nair, Patil, and Mertova 2009); a development that seems to be part of a general decline of student writing abilities in the society (Carter and Harper 2013). Hence, there is an obvious need to train and progressively improve the writing skills during university studies to reach the desired level and there are a number of suggested methods to do this in different disciplines (Berry and Fawkes 2010;Carr 2013;Leydon, Wilson, and Boyd 2014;Walker and Sampson 2013). All these methods have in common that they try to optimise feedback and/or peer-review processes to improve writing skills.…”
Section: Introductionmentioning
confidence: 99%